Assessment of Cardiac Troponin I Responses in Nonhuman Primates during Restraint, Blood Collection, and Dosing in Preclinical Safety Studies. (February 2017) - Reagan, William J.; Barnes, Robert; Harris, Peter; Summers, Sandy; Lopes, Sarah; Stubbs, Makeida; Blackwell, David; Steidl-Nichols, Jill
Limited information has been published on the use of cardiac troponin I (cTnI) as a biomarker of cardiac injury in monkeys. The purpose of these studies was to characterize the cTnI response seen in cynomolgus macaques during routine dosing and blood collection procedures typically used in preclinical safety studies and to better understand the pathogenesis of this response. We measured cTnI using two different methods, the Siemens Immulite cTnI assay and the more sensitive Siemens Troponin I-Ultra assay. We were able to demonstrate that after oral, subcutaneous, or intravenous dosing of common vehicles, as well as serial chair restraint for venipuncture blood collection, that minimal to mild transient increases in cTnI could be detected in monkeys with both assays. cTnI values typically peaked at 2, 3, 4, or 6 hr after sham dosing and returned to baseline at 22 or 24 hr. In addition, marked increases in heart rate (HR) and blood pressure (BP) occurred in monkeys during the restraint procedures, which likely initiated the cTnI release in these animals. Monkeys that were very well acclimated to the chairing procedures and had vascular access ports for blood sampling did not have marked increases in HRs and BP or increases in cTnI.